Participatory Rural Appraisal (PRA) Approach to Bang Pilo Programme Implementation - Dwinanto Kurniawan; M Andri Nugroho; Catharina Siena; Somaya Saragih; Navulani, Niwang Gita (Prospect Publishing, 2024)
Pindang Lombang is a potential product of Lombang village that has been famous since 50 years ago and still exists until now. During this time, Pindang Lombang sellers have many restrictions in their small business, including lack of business management knowledge, product development, use inappropriate packaging, and short consumable product durability. Based on this issue, the Bang Pilo Programme was implemented to address the problems of the Pindang Lombang sellers. The programme implementation method uses a Participatory Rural Appraisal (PRA) approach that emphasises community participation. The programme learning lies in active group participation based on needs, multi-stakeholder cooperation, and prioritisation of programme activities. Through the Bang Pilo Programme, there is an increase in group capacity regarding UMKM managerial, production and packaging standardisation, use appropriate packaging, use of technology in packaging, and product marketing. Active participation is shown in the implementation activities. Through Bang Pilo, a group consisting of Pindang Lombang traders was formed. The success of program implementation lies in (1) the active participation of the community, (2) the cooperation of relevant multi-stakeholders, and (3) the preparation of appropriate program priorities.